Efforts to increase junior high school students confidencethrough assertive training - Susanti, Romia Hari (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2016)
One of important aspects of personality in human life, especially teenagers is confidence. Counseling teachers can increase student confidence through assertive training. Through the training, students are expected to understand that everyone has the right to express their feelings, opinions, beliefs, and attitudes to do a thing without a doubt, but do not hurt other people's feelings, so that confidence can be increased. This study aims to improve students' confidence through assertive training using classroom action research. Subjects in this study were students of SMP Brawijaya Smart School Malang who have low-confidence criteria